1987
DOI: 10.1128/jcm.25.8.1401-1405.1987
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cell culture sensitivity and virus concentration on rapid detection of herpes simplex virus by cytopathic effects and immunoperoxidase staining

Abstract: Tremendous interest has been generated in the commercial kits now available that incorporate herpes simplex virus isolation in cell culture with immunoperoxidase staining for viral antigen detection. Most studies comparing commercial kits with conventional cell culture techniques have found the kits to be less sensitive. However, different cell cultures were used for the two methods. In this study, mink lung, rabbit kidney, MRC-5, and Vero cells were compared for reisolation of herpes simplex virus from clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
(39 reference statements)
1
18
0
1
Order By: Relevance
“…In summary, our study indicates that, as others have reported (2,5,10,12), standard tissue cultures using RK cells demonstrated an enhanced sensitivity for HSV. This system should be considered in laboratory situations requiring maximum sensitivity, such as screening for asymptomatic genital shedding of HSV.…”
Section: Discussionsupporting
confidence: 82%
“…In summary, our study indicates that, as others have reported (2,5,10,12), standard tissue cultures using RK cells demonstrated an enhanced sensitivity for HSV. This system should be considered in laboratory situations requiring maximum sensitivity, such as screening for asymptomatic genital shedding of HSV.…”
Section: Discussionsupporting
confidence: 82%
“…This is especially important in a reference laboratory, since the time involved in specimen transport from outside the institution results in a delay in processing and, most likely, a fall in virus titer. Cell lines more sensitive to HSV, however, such as mink lung cells (6,9) or possibly A549 cells, may be adequate substitutes in rapid centrifugation methods for conventional cell culture and should be further evaluated. Although good results have been obtained with Vero cells (5), Zhao et al (9) demonstrated that this cell lune was less sensitive than MRC-5 cells to infection with HSV.…”
Section: Notesmentioning
confidence: 99%
“…Because the virus is enveloped and highly labile, specimens collected using a swab must be transferred to suitable viral transport media (VTM), such as M4, M6, or universal transport medium, and others [15] . Both rabbit kidney and mink lung cell lines were used for culturing of HSV-1 and HSV-2, with (100% and 95%, respectively) and showed that the sensitivities with a low viral inoculum were higher than those with the MRC-5 and Vero cell lines (77% and 64%, respectively) [17] . Direct immunofluorescence assays (DFA) is another method developed for direct diagnosis of patient specimens which giving the result in one day.…”
Section: Cell Culturementioning
confidence: 99%